Climate change impact on the West African monsoon from June to October. - (:unkn) unknown (My University, 2015)
Sixteen CMIP5 models are used toanalyse how climate changes over the West African Monsoon region between a “future period”, defined from 2031 to 2070under the rcp4.5 emission scenario, and the “current period”, defined from 1960 to 1999 under the historical emissionscenario. The results show an increase of the September to October rainfall amounts. Circulation anomalies include of anincreases of sea-level pressure over the Mediterranean Sea and Europe that allow a strengthening of the moisture flux fromEuro-Mediterranean regions into the Sahel. These changes are stronger in autumn.
Keywords: African Research